2021
DOI: 10.1016/j.ctrv.2021.102258
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional therapies in patients with intrahepatic cholangiocarcinoma: A systematic review and pooled analysis

Abstract: Background: Locoregional treatments (LRT) including radioembolisation (SIRT), transarterial chemoembolisation (TACE), hepatic arterial infusion (HAI) of chemotherapy, external beam radiotherapy (EBRT) and ablation have been studied for the management of intrahepatic cholangiocarcinoma (iCC). The aim of this systematic review was to provide outcome benchmarks for clinical trial design. Methods: Identification of studies reporting outcomes of patients treated with LRT for iCC was performed using PubMed and Embas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 25 publications
1
65
1
Order By: Relevance
“…[ 59 ] A recently published systematic review and pooled analysis of LRTs in iCCA found a pooled mean weighted OS of 18.9 months (95% CI, 14.2–23.5) for EBRT, 14.1 months (95% CI, 12.1–16.0) for radioembolization, 15.9 months (95% CI, 12.9–19.0) for TACE, and 21.3 months (95% CI, 15.4–27.1) for hepatic artery infusion. [ 60 ] Another recent systematic review and meta‐analysis by Mosconi et al specifically evaluated intra‐arterial therapies such as TACE and transarterial radioembolization (TARE). [ 61 ] Thirty‐one articles comprising 1695 patients (TACE, n = 906; TARE, n = 789) were identified.…”
Section: Outcomes With Lrts For Patients With Liver‐only Icca Not Ame...mentioning
confidence: 99%
“…[ 59 ] A recently published systematic review and pooled analysis of LRTs in iCCA found a pooled mean weighted OS of 18.9 months (95% CI, 14.2–23.5) for EBRT, 14.1 months (95% CI, 12.1–16.0) for radioembolization, 15.9 months (95% CI, 12.9–19.0) for TACE, and 21.3 months (95% CI, 15.4–27.1) for hepatic artery infusion. [ 60 ] Another recent systematic review and meta‐analysis by Mosconi et al specifically evaluated intra‐arterial therapies such as TACE and transarterial radioembolization (TARE). [ 61 ] Thirty‐one articles comprising 1695 patients (TACE, n = 906; TARE, n = 789) were identified.…”
Section: Outcomes With Lrts For Patients With Liver‐only Icca Not Ame...mentioning
confidence: 99%
“…However, not all lesions are eligible for ablation. In tumors that are large or unfavorably located for ablation, trans-arterial therapies seem to play an important role [31].…”
Section: Treatment Alternativesmentioning
confidence: 99%
“…A high proportion of patients were down-staged to surgical intervention and had favorable post-surgical outcomes. The results of other studies confirmed the promising outcomes with the locoregional treatment of ICCs; however, this should be confirmed in randomized studies [ 17 ].…”
Section: Introductionmentioning
confidence: 59%
“…A multiple single-center series reported the results of SIRT among patients with locally advanced ICCs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Systematic reviews have suggested the activity of a SIRT treatment as well as other locoregional therapies [ 17 , 30 , 31 ]. The efficacy of SIRT has recently been confirmed with an acceptable safety profile in the prospective MISPHEC trial [ 16 ].…”
Section: Discussionmentioning
confidence: 99%